2017
DOI: 10.3892/mmr.2017.8262
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid‑induced expression of nicotinamide adenine dinucleotide phosphate‑diaphorase in the immune organs of mice: A possible role of nitric oxide in immunomodulation

Abstract: The aim of the present study was to investigate the effects of betulinic acid (BetA) on the expression and distribution pattern of nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d), an indirect indicator of nitric oxide (NO) synthase in the thymus and spleen of mice. Mice were randomly assigned to four main groups (n=48 per group): Experimental group (BetA), positive control group (goniothalamin), vehicle control group (dimethyl sulfoxide) and control group (without vehicle). Each group was furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…GC/MS was used to examine Al-Baha date palm kernel (AB-DPK) extract. Antioxidants like 1-Trilinolein and (Z,Z) 3Dioctadecenoyl Glycerol as well as anti-tumor, anti-inflammatory, and antiviral medicines like botulin were among the compounds discovered in the investigation [ 85 , 86 ]. Extracts of the flesh and pits of dates were evaluated to ameliorate CCl4-induced hepatotoxicity in a rat model, and the extracts displayed significant hepatoprotective activity for animals that received the date extracts [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…GC/MS was used to examine Al-Baha date palm kernel (AB-DPK) extract. Antioxidants like 1-Trilinolein and (Z,Z) 3Dioctadecenoyl Glycerol as well as anti-tumor, anti-inflammatory, and antiviral medicines like botulin were among the compounds discovered in the investigation [ 85 , 86 ]. Extracts of the flesh and pits of dates were evaluated to ameliorate CCl4-induced hepatotoxicity in a rat model, and the extracts displayed significant hepatoprotective activity for animals that received the date extracts [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-d), an indirect indicator of NO synthase in the thymus and spleen. Pang et al ( 2018 ) suggested that betulinic acid upregulated the expression of NADPH-d activity and that NO signaling may be a potential mechanism underlying betulinic acid-induced immunomodulation in the thymus and spleen (Pang et al 2018 ).…”
Section: Oleanane Type Triterpenesmentioning
confidence: 99%
“…Betulinic acid, a pentacyclic triterpenoid, is widely found in the medicinal plants (Gauthier et al, 2011), including Bacopa monniera Diospyros bipindensis (Viji et al, 2010), (Brusotti et al, 2017), (James and Dubery, Centella asiatica 2009), (Qian et al, 2012) etc. Betulinic acid Zizyphi spinosi was reported to have a wide spectrum of pharmacological activities such as, antioxidant (Yamashita et al, 2002), antiinflammatory (Viji et al, 2010), antimalarial (de Sá et al, 2009, antidiabetic (Alqahtani et al, 2013), antidepressant (Machado et al, 2013), anti-HIV (Fujioka et al, 1994), antihepatitis C (Lin et al, 2015), antineoplasic (Fulda, 2009) and immunomodulatory activities (Pang et al, 2018). In addition, betulin or its bioactive derivative betulinic acid showed neuroprotective effects in cerebral ischemiareperfusion injury (Lu et al, 2011), Parkinson's disease (Tsai et al, 2017), epilepsy (Muceniece et al, 2008), amyloid beta-induced neurotoxicity (Planchard et al,2012) and multiple sclerosis (Blazevski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%